In Silico analysis, prediction and ranking of Drug binding affinity of Cyclooxygenase-2(COX2) and Nuclear Factor KappaB (NFkB) using Curcumin and its analogues in Cancer Treatment - B Athira; S Lakshmi Priyadarsini (BIO Web of Conferences)
This present study investigates the binding affinities of curcumin and its derivatives with Nuclear Factor Kappa B(NF-kB) and Cyclooxygenase-2(COX-2), the most targeted molecules in oncological therapies. Employing insilico techniques, particularly molecular docking through Swiss Dock, ten conformers of curcumin were evaluated for their interactions with these proteins. As per the docking analysis, Bisdemethoxycurcumin exhibited the most favorable binding energies, signifying the strongest affinity for both NF-kB(-2218.61 kcal/mol) and COX-2(-1156.81kcal/mol). Moreover, Tetrahydrocurcumin and Demethoxycurcumin showed -promising binding affinities. The above observation simply that the curcumin derivatives, especially Bisdemethoxycurcumin, exhibit considerable potential as therapeutic agents for the inhibition of vital pathways associated with malignant transformation. The present research lead thread to future investigations into the creation of curcumin-based inhibitors aimed at NF-kB and COX-2 in cancer treatment.